2012
DOI: 10.1186/1475-2891-11-81
|View full text |Cite
|
Sign up to set email alerts
|

Synbiotics, probiotics or prebiotics in infant formula for full term infants: a systematic review

Abstract: BackgroundSynbiotics, probiotics or prebiotics are being added to infant formula to promote growth and development in infants. Previous reviews (2007 to 2011) on term infants given probiotics or prebiotics focused on prevention of allergic disease and food hypersensitivity. This review focused on growth and clinical outcomes in term infants fed only infant formula containing synbiotics, probiotics or prebiotics.MethodsCochrane methodology was followed using randomized controlled trials (RCTs) which compared te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
116
2
7

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 132 publications
(130 citation statements)
references
References 80 publications
(311 reference statements)
5
116
2
7
Order By: Relevance
“…41 Prebiotics in formula increased weight gain but had no impact on length or head circumference. 22,42 However, the quality of this evidence is compromised by imprecision, inconsistency of results, use of different study preparations and publication bias. 42 With a GOS/FOS mixture, growth was normal and similar to a standard infant formula.…”
Section: Prebiotics and Growthmentioning
confidence: 99%
See 1 more Smart Citation
“…41 Prebiotics in formula increased weight gain but had no impact on length or head circumference. 22,42 However, the quality of this evidence is compromised by imprecision, inconsistency of results, use of different study preparations and publication bias. 42 With a GOS/FOS mixture, growth was normal and similar to a standard infant formula.…”
Section: Prebiotics and Growthmentioning
confidence: 99%
“…22,42 However, the quality of this evidence is compromised by imprecision, inconsistency of results, use of different study preparations and publication bias. 42 With a GOS/FOS mixture, growth was normal and similar to a standard infant formula. 38,43 A multi-center, randomized, double-blind, placebo-controlled trial including 1130 healthy term infants showed a similar mean weight, length and head circumference, skin fold thicknesses and arm circumference evolution in all infants.…”
Section: Prebiotics and Growthmentioning
confidence: 99%
“…In addition, a large number of clinical trials in term of infants have shown controversial results related to the increase in Biidobacteria in feces due to supplementation of infant formula with GOS and FOS. A systematic review published by Rao et al [78] reported that some of the randomized controlled trials (RCTs) showed a trend of increasing Biidobacteria counts in formula supplemented fed infants, and another systematic review published by Mugambi et al [81] failed to show the increase in Biidobacteria or Lactobacillus or the decrease of pathogens in infants fed with prebiotic supplemented formula.…”
Section: Type Of Infant Feedingmentioning
confidence: 99%
“…Prebiotics are able to change gut metabolic activity, bring stool consistency, and defecation frequency closer to that of breastfed infants. Other outcomes included beter weight gain and softer stools, and a signiicant reduction in stool pH for infants who received prebiotic supplementation [78,81]. Moreover, prebiotics have been used to prevent or treat obesity.…”
Section: Type Of Infant Feedingmentioning
confidence: 99%
“…A different approach could be administration of live microorganisms, as has been attempted with probiotic and synbiotic preparations containing a small number of allegedly beneficial bacteria. Although these preparations are currently widely used, their benefit for allergic diseases (34) or for infant health in general (35) has not been clearly established. Moreover, a recent, large, placebo-controlled, randomized trial of the use of lactobacilli and bifidobacteria in the prevention of antibiotic-associated diarrhea due to Clostridium difficile showed no benefit (36).…”
Section: Parker B Francis Lecturementioning
confidence: 99%